Influence of source materials and the role of oxide composition on the performance of ternary blended sustainable geopolymer mortar. (30th July 2017) - Sharmin, Afia; Alengaram, U. Johnson; Jumaat, Mohd Zamin; Yusuf, Moruf Olalekan; Kabir, S.M. Alamgir; Bashar, Iftekhair Ibnul
Highlights: High rate of geopolymerization resulted in achievement of 3 day strength. Lower difference in strength between mixes with 14 M and 12 M with high percentages of GGBS. Ternary combination of RHA, GGBS and MK achieved higher strength than binary combination. Unreactive particles of RHA reduced strength of mortar with high volume of RHA. Amorphorsity of mortar increased with the increase in percentage of MK as binder. Abstract: This research article reports the contribution of different oxides present in rice husk ash (RHA), ground granulated blast furnace slag (GGBS) and metakaolin (MK) on the performance of geopolymer mortars. Twenty-six mixes were designed with combined base materials and varied NaOHaq concentration, that was used as one of the activators. RHA, GGBS and MK contents were varied between 15% and 70%, 0% and 75%, and 0% and 40%, respectively. The binder/fine aggregate, water/binder and alkaline activator/binder ratios were kept constant while all the specimens were cured at 65 °C for 24 h. The mixture (ternary) that contained 25% RHA, 25% MK and 50% GGBS (M25 R25 G50 ) produced the highest compressive strength of 48 MPa; in addition, it produced better flow rate and lower density than any binary combinations. The findings through microstructural and characterization tools show that regardless of the source, SiO2 and CaO present in the base materials contributed to the strength, while Al2 O3 influenced the amorphorsity of the products.